The diet of a roosting population of Asian glossy starling aplonis panayensis in Jelebu, Negeri Sembilan, Malaysia - Noorul Ezyan Nor Hashim; Mohammad Saiful Mansor; Nurul Ashikin Abdullah; Rosli Ramli (Penerbit Universiti Kebangsaan Malaysia, 2021)
Communal roosting by urban birds, such as crows, mynas, and starlings, can be a public nuisance due to excessive noise and fouling of the surroundings with droppings. Food availability within proximity to the roosting area is one of the key factors influencing roosting site preference and fidelity. The diets of roosting mynas and crows have been well-studied, yet little is known about the diet of the Asian glossy starling (AGS), Aplonis panayensis. This study focused on assessing the diet of roosting AGS and food resource availability around the roosting area. The AGS diet was assessed through microscopic analysis of stomach contents and droppings. The diet mainly consisted of fruits (76%) with a minor component of animal materials, i.e. ants, snails, and beetle larvae. Intact seeds found in the samples were identified using DNA barcoding. Seven out of the nine plant species detected were new records for the AGS diet. The most common fruit found in the samples was Trema orientalis, which grows extensively along roadsides within foraging areas of AGS. The availability of fruits of different fast-growing pioneer species around the roosting site ensured a continuous supply of food to the birds. Animal materials, which were consumed by chance during foraging, supplemented the fruit in the bird’s diet. Hence, the birds’ preference for the roosting site may have been influenced by the availability of various food resources around it.